Vestibular Perceptual Thresholds Increase above the Age of 40 - Bermúdez Rey, María Carolina; Clark, Torin K.; Wang, Wei; Leeder, Tania; Bian, Yong; Merfeld, Daniel M. (Frontiers in Neurology, 2016)
We measured vestibular perceptual thresholds in 105 healthy humans (54F/51M) ranging from 18 to 80 years of age. Direction-recognition thresholds were measured using standard methods. The motion consisted of single cycles of sinusoidal acceleration at 0.2 Hz for roll tilt and 1.0 Hz for yaw rotation about an earth-vertical axis, inter-aural earth-horizontal translation (y-translation), inferior-superior earth-vertical translation (z-translation), and roll tilt. A large subset of this population (99 of 105) also performed a modified Romberg test of standing balance. Despite the relatively large population (54F/51M), we found no difference between thresholds of male and female subjects. After pooling across sex, we found that thresholds increased above the age of 40 for all five motion-directions investigated. The data were best modeled by a two-segment age model that yielded a constant baseline below an age cut-off of about 40 and a threshold increase above the age cut-off. For all subjects who passed all conditions of the balance test, the baseline thresholds were 0.97˚/s for yaw rotation, 0.66˚/s for 1Hz roll tilt, 0.35˚/s for 0.2Hz roll tilt, 0.58cm/s for y-translation, and 1.24cm/s for z-translation. As a percentage of the baseline, the fitted slopes (indicating the threshold increase each decade above the age cut-off) were 83% for z-translation, 56% for 1Hz roll tilt, 46% for y-translation, 32% for 0.2Hz roll tilt, and 15% for yaw rotation. Even taking age and other factors into consideration, we found a significant correlation of balance test failures with increasing roll tilt thresholds.